Benign thyroid disease and vocal cord palsy. - Rowe-Jones, J. M. (Royal College of Surgeons of England, 1993)
The case notes of 2453 consecutive patients admitted for thyroid surgery and with successful preoperative laryngoscopy were examined retrospectively. Of the 2408 patients who had not had previous operations on the gland, 2321 proved to have benign pathology. A total of 29 patients had a preoperative vocal cord palsy of which 22 were associated with benign disease. Return of cord movement after surgery occurred in 89% of the patients with a benign goitre. We advocate routine preoperative laryngoscopy to detect vocal cord paresis. Such a finding with a goitre does not necessarily indicate malignancy. The recurrent laryngeal nerve should therefore be identified at surgery and preserved to allow for recovery of vocal cord movement.